2018
DOI: 10.1038/s41598-018-21234-y
|View full text |Cite
|
Sign up to set email alerts
|

Counting the electrons in a multiphoton ionization by elastic scattering of microwaves

Abstract: Multiphoton ionization (MPI) is a fundamental first step in high-energy laser-matter interaction and is important for understanding the mechanism of plasma formation. With the discovery of MPI more than 50 years ago, there were numerous attempts to determine the basic physical constants of this process in direct experiments, namely photoionization rates and cross-sections of the MPI; however, no reliable data was available until now, and the spread in the literature values often reaches 2–3 orders of magnitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…These authors found rate coefficents for photoionization between 10 −9 to 10 −15 cm 3 s −1 depending on the electron temperature and density [10]. Other photoionization rates have been reported [11], but these rates describe multi-photon ionization during the formation of LPPs and thus are not applicable to the CR model considered here. However, it is noteworthy that these high photoionization rates during the laser pulse duration play a significant role in creating LPPs when the laser beam is of sufficient intensity.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…These authors found rate coefficents for photoionization between 10 −9 to 10 −15 cm 3 s −1 depending on the electron temperature and density [10]. Other photoionization rates have been reported [11], but these rates describe multi-photon ionization during the formation of LPPs and thus are not applicable to the CR model considered here. However, it is noteworthy that these high photoionization rates during the laser pulse duration play a significant role in creating LPPs when the laser beam is of sufficient intensity.…”
Section: Introductionmentioning
confidence: 87%
“…Comparing the order of magnitude of the photoionization rate coefficients determined by Su et al with the multi-photon rate coefficients, clearly shows the difference between the two. For the photoionization of O (Z A = 8) with laser intensities on the order of 10 13 W/cm −2 , Sharma et al report the multi-photon rates being between 10 8 to 10 10 s −1 , where n e is on the order of 10 14 to 10 15 cm −3 [11], corresponding to rate coefficients between 10 −6 to 10 −5 cm 3 s −1 . The resonant process of dielectronic recombination (DR) has recently been shown to have a significant effect upon the charge state distribution of Si (Z A = 14) LPPs [12].…”
Section: Introductionmentioning
confidence: 99%
“…( 5 ), the electron density N e ( ξ ) is dominated by the ionization rate associated with the incident laser intensity I ( ξ ) 33 , which gradually increases with I ( ξ ) and reaches a maximum increment at the peak. However, because the electron–ion recombination time is usually much longer than the femtosecond scale of the pulse width 34 , 35 , N e ( ξ ) should be considered static after the peak. Therefore, the first term on the r.h.s.…”
Section: Resultsmentioning
confidence: 99%
“…Notable advantages of the technique include a high sensitivity, good temporal resolution, low shot noise 11 , non-intrusive probing, and the capability of time gating due to continuous scanning. The advantages of CMS over other available diagnostic techniques (microwave interferometry, laser interferometry, time-of-flight mass spectrometry, laser Thomson scattering, Langmuir probes, hairpin resonators) refer to limited sensitivities, lack of absolute calibration, necessity of signal accumulation, and plasma perturbations of the latter as previously reported elsewhere 5 , 17 .…”
Section: Introductionmentioning
confidence: 89%
“…A careful understanding of electromagnetic-plasma and scattering interactions is essential for the proper extraction of information on total electron numbers and subsequent derivable quantities (e.g., the electron number density ) from CMS. Vast historical art exists for weakly-ionized, strongly collisional microplasmas in which electron motion is restricted by electron-neutral collisions 4 , 5 , 9 , 10 . However, application of the diagnostic to collisionless plasmas has remained relatively unexplored (no N e correspondence is given by 11 , 13 , 18 )—despite garnering some attention in recent years 19 due to a prevalence in studies on electric propulsion devices 20 , photoionization in low-pressure conditions 21 , 22 , etc.…”
Section: Introductionmentioning
confidence: 99%